Bovine lactoferrin inhibits SARS‐CoV‐2 and SARS‐CoV‐1 by targeting the RdRp complex and alleviates viral infection in the hamster model. Issue 1 (1st December 2022) - He, Shi‐ting; Qin, Hongbo; Guan, Lin; Liu, Ke; Hong, Bixia; Zhang, Xiaoxu; Lou, Fuxing; Li, Maochen; Lin, Wei; Chen, Yangzhen; He, Chengzhi; Liu, Feitong; et al.
Abstract: Breast milk has been found to inhibit coronavirus infection, while the key components and mechanisms are unknown. We aimed to determine the components that contribute to the antiviral effects of breastmilk and explore their potential mechanism. Lactoferrin (Lf) and milk fat globule membrane inhibit severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐related coronavirus GX_P2V and transcription‐ and replication‐competent SARS‐CoV‐2 virus‐like particles in vitro and block viral entry into cells. We confirmed that bovine Lf (bLf) blocked the binding between human angiotensin‐converting enzyme 2 and SARS‐CoV‐2 spike protein by combining receptor‐binding domain (RBD). Importantly, bLf inhibited RNA‐dependent RNA polymerase (RdRp) activity of both SARS‐CoV‐2 and SARS‐CoV in vitro in the nanomolar range. So far, no biological macromolecules have been reported to inhibit coronavirus RdRp. Our result indicated that bLf plays a major role in inhibiting viral replication. bLf treatment reduced viral load in lungs and tracheae and alleviated pathological damage. Our study provides evidence that bLf prevents SARS‐CoV‐2 infection by combining SARS‐CoV‐2 spike protein RBD and inhibiting coronaviruses' RdRp activity, and may be a promising candidate for the treatment of coronavirus disease 2019.